2020
DOI: 10.1186/s12889-020-09067-9
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic development and pregnancy mental health: secondary analyses of data from rural Vietnam

Abstract: Background: This study aimed to establish whether changes in the socioeconomic context were associated with changes in population-level antenatal mental health indicators in Vietnam. Methods: Social, economic and public policies introduced in Vietnam (1986-2010) were mapped. Secondary analyses of data from two cross-sectional community-based studies conducted in 2006 (n = 134) and 2010 (n = 419), involving women who were ≥ 28 weeks pregnant were completed. Data for these two studies had been collected in struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…This strategy would rely on improved multi-sectoral action and collaboration. This result is in line with a recent study that suggested that IPV could be reduced by improving household wealth because this change would have a positive impact on women's socioeconomic and political contexts (Stocker et al, 2020). Le et al (2019) (Tokhi et al, 2018).…”
Section: Feasibility Of the Adapted Inspire Frameworksupporting
confidence: 92%
See 2 more Smart Citations
“…This strategy would rely on improved multi-sectoral action and collaboration. This result is in line with a recent study that suggested that IPV could be reduced by improving household wealth because this change would have a positive impact on women's socioeconomic and political contexts (Stocker et al, 2020). Le et al (2019) (Tokhi et al, 2018).…”
Section: Feasibility Of the Adapted Inspire Frameworksupporting
confidence: 92%
“…A recent national survey in 2020 examining violence against women in Vietnam found that two in three women (62.9%) experienced at least one type of IPV in their lifetime (emotional IPV -47%, physical IPV -26.1%, sexual IPV -13.3%) (United Nations Population Fund Vietnam, 2020). Further, mounting evidence shows the adverse maternal outcomes of p-IPV exposure in Vietnam including common mental disorders (CMD) (Hoang et al, 2016), especially postnatal depression (PPD) and anxiety (Fisher et al, 2010;Murray et al, 2015;Stocker et al, 2020) and having suicidal ideation (Fisher et al, 2013c).…”
Section: Context Looking Through the Lens Of The Vietnamese Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, research suggests that 10% of pregnant women experience some type of mental disorder. 1 , 2 However, a review by Fisher et al revealed that approximately 15% of women in low- and middle-income countries (LMICs) experience common mental disorders (CMDs), such as depression, anxiety and adjustment disorders, antenatally and 20% postnatally. 1 Despite the disproportionate burden of CMDs among pregnant women in LMICs, the perinatal mental health of women in such contexts has received significantly less scholarly attention.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Notably, women who experience CMDs during pregnancy are less likely to attend antenatal care and more likely to report substance misuse and lower than expected weight gain. 2 This may not only result in adverse obstetric outcomes for the woman, such as intrauterine growth restriction, but can have adverse consequences for the child. Wachs et al have shown that children of depressed mothers living in LMICs experience cognitive and motor delay, as well as undernutrition and stunting.…”
Section: Introductionmentioning
confidence: 99%